Open IACS: apertura, interoperabilità e riuso dati dai sistemi integrati di gestione e controllo per i pagamenti in agricoltura - Flavio Lupia (mediaGEO soc. coop., 2021)
Open LOD platform based on HPC capabilities for Integrated Administration and Control System of Common Agrarian Policy (Open IACS) is an EU funded project (4.5 MEur) fostering the administrative data reuse in the context of the Common Agricultural Policy (CAP) and granting open access to farmers, policy makers and third parties. Data from European paying agencies for agriculture will be harmonised, and a network of Linked Open Data will be developed. An interoperable system of EU High Performance Computing Centres will provide a platform for demonstrating different use case scenarios (e.g. applications for computing CAP performance indicators, climate change indicators and integration between environmental and agricultural data).